Line impedance compensation control strategy for multiple interlinking converters in hybrid AC/DC microgrid. Issue 6 (30th December 2022) - Wang, Can; Deng, Can; Pan, Xuewei
Abstract: In a hybrid AC/DC microgrid (MG), the interlinking converter (IC) plays an important role in power flow regulation between subgrids. However, line impedance will cause deviations in the power transmitted by the IC if a communication device is not used. To realize accurate power delivery between subgrids without communication, an IC control method based on line impedance compensation is proposed. A harmonic signal is injected into the IC in this method using converters of distributed generation, which are connected to an AC bus. The specified frequency of the signal indicating the voltage of the AC bus can be acquired by an IC using a filter and phase‐locked‐loop (PLL) so that the IC can obtain line impedance by local information and then compensate for voltage drop to realize accurate power transmission. The entire implementation of this method uses no communication. Moreover, when multiple ICs run in parallel, this method can also be conducted easily and effectively to realize accurate power flow between subgrids and power sharing among ICs in proportion to the ICs' rated capacity. This strategy is verified by simulation and hardware‐in‐the‐loop tests. Abstract : A control method based on line impedance compensation for low‐voltage hybrid microgrids is proposed in this manuscript. The proposed method can detect line resistance and realize accurate power transmission between subgrids using no communication devices. Furthermore, the proposed method can also be applied for multiple interlinking converters (ICs) running in parallel to realize power sharing among the ICs.